ACUPUNCTURE TREATMENT IN PATIENT WITH INFERTILITY - Zhu, Jihe; Arsovska, Blagica; Kozovska, Kristina (International Journal of Research -GRANTHAALAYAH, 2018)
Acupuncture as part of the Traditional Chinese Medicine (TCM) is used very often as a treatment option for patients struggling with infertility. Acupuncture can help in regulating the hormonal imbalances, relieve the stress and increase the blood flow to the ovaries and uterus. The treated patient is 30 year old woman diagnosed with polycystic ovarian syndrome (PCOS) and infertility. The patient was trying to get pregnant for a year and a half. The menstrual cycles were irregular and the patient was taking the medication Diane for 4 years. The hormonal analysis showed high FSH levels and low Estrogen and Progesterone. The patient has done 6 treatments in a period of two months and after the 6th treatment she got pregnant. Treatments were done in a clinic for TCM and acupuncture in Skopje, Macedonia by a doctor specialist in acupuncture. Treatments were with duration of 30-45 minutes, done once weekly on points located on the both sides of the body. The treated points are: Ex-CA1 (Zigongxue), Gv20 (Baihui), St25 (Tianshu), St36 (Zusanli), Ren12 (Zhongwan), Ren6 (Qihai), Ren2 (Qugo), Sp6 (Sanyinjiao), Li4 (Hegu), Lv3 (Taichong) and Ashi points located on front side of the neck. Acupuncture as a treatment for infertility is very effective and gives excellent results by improving the hormonal levels, the menstruation and the ovulation in women, thus giving a chance to the patients to become pregnant.